The gravitational force of mental health services: distance decay effects in a rural Swiss service area - Niklaus Stulz; Eva-Maria Pichler; Wolfram Kawohl; Urs Hepp (BMC, 2018)
Abstract Background Previous research suggested a distance decay effect in health services systems, with people living closer to service facilities being more likely to use them. Method In this ecological cross sectional study, we conducted spatial and statistical analyses in a Swiss mental health services system being legally bound to provide primary mental health care to approximately 620,000 inhabitants. We examined a cohort of all patients who were over 18 years old and who were treated in the mental health services system between January and December 2011. Results There were 5574 treatment cases during the 12-month period, 2161 inpatient cases and 3413 outpatient cases. Travel time by public transportation between patients' residence and the closest mental health service facility negatively predicted the utilization of outpatient services for all mental disorders, even after controlling for variability in ecological (e.g. socioeconomic) characteristics of the communities in the service provision area. For utilization of inpatient wards no geographical distance decay effect was observed, except for organic mental disorders. Conclusions Based on these findings, outpatient clinics should be most effectively located decentralized and in the largest communities to meet the needs of the population as close as possible to where people live and to avoid remote areas being insufficiently supplied with mental health care. For mental hospitals and inpatient services decentralized location seems to be less important.